PERAN KOMPETENSI KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERIKANAN KOTA PALOPO - Rezky Auliyah Faizal; Samsul Bachri; Suhandra Makkasau (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study aims to determine how much influence and role of competence and work discipline have on the work productivity of employees at the Fisheries Office of the city of Palopo. In this study the authors used quantitative research methods, the sample used was the entire population of 85 people. The result of the research is that competence has a significant effect on employee work productivity. Work discipline has a significant effect on employee work productivity. The coefficient of determination obtained by R Square is 0.549 or 54.9%, which means that the effect of workload and work discipline on employee productivity at the Palopo City Fisheries Service is 54.9%, and the remaining 45.1% is influenced by other variables that are not examined in this study, such as motivation, job satisfaction, compensation, organizational culture, work environment, and other variables.